Compulsory Disclosure of Private Information - Theoretical and Experimental Results for the Acquiring-a-Company Game - Alexandra Zaby; Werner Güth; Kerstin Pull; Manfred Stadler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Based on the acquiring-a-company game of Samuelson and Bazerman (1985), we theoretically and experimentally analyze the acquisition of a firm. Thereby we compare cases of symmetrically and asymmetrically informed buyers and sellers. This setting allows us to predict and test the effects of information disclosure as prescribed by two recently implemented directives of the European Union, the Transparency and the Takeover-Bid Directive. Our theoretical and experimental results suggest a welfare-enhancing effect of compulsory information disclosure. Hence, the EU Transparency and the EU Takeover-Bid Directive should both be welfare enhancing.
Keywords: C91; D82; D61; 330